2020
DOI: 10.1177/0022022120966786
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Functioning Behaviors for Trauma-Affected Children in the Cambodian Context

Abstract: Across contexts, the roles and responsibilities for children are shaped by a range of sociocultural factors; thus, a contextually specific exploration of adaptive functioning norms is important in optimizing the acceptability, effectiveness, and sustainability of mental health intervention and community programming. The current study aimed to examine child adaptive functioning behaviors for children in Cambodia, a country faced with continuing recovery efforts from war and genocide, intergenerational trauma tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…One possible mechanism for such an effect could be culture-specific life functioning indicators among Cambodian children. This possibility is supported by research by Figge and colleagues, who found that helping others is a central life functioning expectation for Cambodian children (Figge et al, 2020), in contrast in Western cultures where it is less central (Bird et al, 2005). Thus, an important area for future research will be the development and use of culture-specific life functioning indicators, to more fully assess the convergent validity of culture-specific psychopathology measures.…”
Section: Limitationsmentioning
confidence: 93%
“…One possible mechanism for such an effect could be culture-specific life functioning indicators among Cambodian children. This possibility is supported by research by Figge and colleagues, who found that helping others is a central life functioning expectation for Cambodian children (Figge et al, 2020), in contrast in Western cultures where it is less central (Bird et al, 2005). Thus, an important area for future research will be the development and use of culture-specific life functioning indicators, to more fully assess the convergent validity of culture-specific psychopathology measures.…”
Section: Limitationsmentioning
confidence: 93%